2018
DOI: 10.1177/1934578x1801300408
|View full text |Cite
|
Sign up to set email alerts
|

A New Saponin with Anti-HIV-1 Protease Activity fromAcacia pennata

Abstract: We investigated the phytochemicals from an ethanol extract of Acacia pennata (L.) Willd stems, a Vietnam medicinal plant, which led to the isolation of a new saponin termed 21β- O-[(2 E)-6-hydroxyl-2,6-dimethyl-2,7-octadienoyl] pitheduloside G (1), as well as pitheduloside G (2), a known saponin. The structures of compounds 1 and 2 were elucidated via spectroscopy and compared with those reported in the literature. The isolates (1 and 2) were tested for their inhibitory effects on human immunodeficiency virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The study was initially proposed to limit the virtual screening to isolated flavonoids only. However, a literature survey revealed that a saponin ‘21β- O -[(2 E )-6-hydroxyl-2,6-dimethyl-2,7-octadienoyl] pitheduloside G’ isolated from A. pennata exhibited an antiviral activity [ 30 ]. Therefore, in addition to flavonoids, the chances to find a potential lead from other classes of secondary metabolites also exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was initially proposed to limit the virtual screening to isolated flavonoids only. However, a literature survey revealed that a saponin ‘21β- O -[(2 E )-6-hydroxyl-2,6-dimethyl-2,7-octadienoyl] pitheduloside G’ isolated from A. pennata exhibited an antiviral activity [ 30 ]. Therefore, in addition to flavonoids, the chances to find a potential lead from other classes of secondary metabolites also exist.…”
Section: Discussionmentioning
confidence: 99%
“…The bark of A. pennata is also traditionally used to treat gastrointestinal ailments like cholera and dysentery [ 25 , 29 ]. Pharmacological activities like antiviral [ 30 , 31 ], anti-inflammatory, antinociceptive [ 32 ], antioxidant [ 25 ], anti-parasitic [ 33 ], antimicrobial [ 34 ], and antidiabetic [ 35 ] had been scientifically investigated for A. pennata . The traditional utility of A. pennata to treat various health ailments may be attributed to the presence of flavonoids [ 26 ], terpenoids [ 27 ], phenols [ 28 ], and saponins [ 30 ] in the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acacia pennata L., is a thorny woody climber distributed in South and Southeast Asia including India, China and Thailand (Lalchhandama 2013 ). Traditionally, it has been used in rheumatism, headaches and fever treatment (Nguyen et al 2018 ). Several biological reports have been performed on different plant parts, leaves possessed anti-nociceptive, anti-inflammatory (Dongmo et al 2005 ) and antifungal effects particularly towards C. albicans and K. polysporus (Malabadi and Vijay Kumar 2007 ) as well as anti-transcription activities (Rifai et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A. pennata (Family: Fabaceae) is a large thorny plant found in Bangladesh, Bhutan, India, Myanmar, Southwest China, Sri Lanka, Thailand and Vietnam. [14][15][16] There are plenty of nutrients present in A. pennata ( Figure 2) that accounts for its nutraceutical potential. 15 However, specifications on the plant part, method of preparation, route of administration, and dosing regimen adopted for the traditional treatment against malaria were missing.…”
Section: Introductionmentioning
confidence: 99%